Analysis of Adaptive Scheduling Production Planning in Palembang’s Jumputan Industry - Shabila Fitri Aulia; Muhammad Izman Herdiansyah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Destination Palembang has some cultural heritages, one of that is the jumputan fabric. One of the jumputan fabric production places in Palembang is the Griya Tuan Kentang Industry. However, in the process, the production of jumputan fabric still uses a manual process including scheduling the production process.  This study aims to analyze the management of jumputan production scheduling in the Griya Tuan Kentang Industry.  The population of this study was 20 craftsmen but the researcher only conducted interviews with 1 craftsman as the owner of Juanda jumputan.  This research was conducted using qualitative descriptive analysis methods. Data analysis techniques using descriptive qualitative are one type of research whose research result research is not obtained through statistical procedures or other quantification methods.  The results of this study were carried out by trying the number of orders based on sales history in April 2022Based on sales history in April 2022, there are 6 orders for 735 sheets with a size of 3 x 1.5 m with a total number of workers of 143 persons who have their respective duties and responsibilities per stage so that all orders can be completed within 87 days.